Kinematics and Age of Syn‐Intrusive Detachment Faulting in the Southern Alps: Evidence for Early Permian Crustal Extension and Implications for the Pangea A Versus B Controversy. Issue 10 (15th October 2018) - Pohl, Florian; Froitzheim, Nikolaus; Obermüller, Gerrit; Tomaschek, Frank; Schröder, Oliver; Nagel, Thorsten J.; Sciunnach, Dario; Heuser, Alexander
Abstract: Permian basin formation and magmatism in the Southern Alps of Italy have been interpreted as expressions of a WSW‐ENE‐trending, dextral megashear zone transforming Early Permian Pangea B into Late Permian Pangea A between ~285 and 265 Ma. In an alternative model, basin formation and magmatism resulted from N‐S crustal extension. To characterize Permian tectonics, we studied the Grassi Detachment Fault, a low‐angle extensional fault in the central Southern Alps. The footwall forms a metamorphic core complex affected by upward‐increasing, top‐to‐the‐southeast mylonitization. Two granitoid intrusions occur in the core complex, the synmylonitic Val Biandino Quartz Diorite and the postmylonitic Valle San Biagio Granite. U‐Pb zircon dating yielded crystallization ages of 289.1 ± 4.5 Ma for the former and 286.8 ± 4.9 Ma for the latter. Consequently, detachment‐related mylonitic shearing took place during the Early Permian and ended at ~288 Ma, but kinematically coherent brittle faulting continued. Considering 30° anticlockwise rotation of the Southern Alps since Early Permian, the extension direction of the Grassi Detachment Fault was originally ~N‐S. Even though a dextral continental wrench system has long been regarded as a viable model at regional scale, the local kinematic evidence is inconsistent with this and, rather, supports N‐S extensional tectonics. Based on a compilation of >200 U‐Pb zircon ages, we discuss the evolution and tectonic framework of Late Carboniferous to Permian magmatism in the Alps. Key Points: Early Permian metamorphic core complex and extensional detachment fault are reconstructed in the Orobic Anticline (Southern Alps) Two synkinematic to postkinematic plutons in the metamorphic core complex are dated at ~289 and ~287 Ma by U‐Pb LA‐ICP‐MS on zircon Early Permian tectonics represent N‐S extension rather than dextral wrenching related to the Pangea B to A transformation